Preventing Violence in Relationships: Interventions Across the Life Span. 2002
DOI: 10.1037/10455-007
|View full text |Cite
|
Sign up to set email alerts
|

Fostering men's responsibility for preventing sexual assault.

Abstract: Men must take responsibility for preventing sexual assault, because most assaults are perpetrated by men against women, children, and other men. Even though only a minority of men may commit sexual assault, all men can have an influence on the culture and environment that allows other men to be perpetrators. Thus, effective sexual assault prevention requires that men look at their own potential for violence as well as take a stand against the violence of other men. This chapter provides an overview of the issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(146 citation statements)
references
References 35 publications
2
143
0
Order By: Relevance
“…Berkowitz (2002) proposed that men who believe that their peers are using coercion to obtain sex are more likely to show similar behavior themselves. Indeed, students tended to underestimate their peers' attitudes regarding the importance of consent in sexual activities, so the correction of such misperceptions could be an important resource in the prevention of sexual violence (Fabiano, Perkins, Berkowitz, Linkenbach, & Stark, 2003).…”
Section: Evidence For the Effects Of Rape Myth Acceptance As A Socialmentioning
confidence: 99%
“…Berkowitz (2002) proposed that men who believe that their peers are using coercion to obtain sex are more likely to show similar behavior themselves. Indeed, students tended to underestimate their peers' attitudes regarding the importance of consent in sexual activities, so the correction of such misperceptions could be an important resource in the prevention of sexual violence (Fabiano, Perkins, Berkowitz, Linkenbach, & Stark, 2003).…”
Section: Evidence For the Effects Of Rape Myth Acceptance As A Socialmentioning
confidence: 99%
“…The Reactions to Offensive Language and Behavior Scale (ROLBA) is a 26-item self-report scale, adapted from questions used by Berkowitz (2002), which measures men's degree of discomfort with and willingness to confront the inappropriate behavior of other men, as well as their perceptions of other men's discomfort with and willingness to confront these behaviors. This scale yields four subscales; however, only the Self Prosocial Bystander Behavior subscale was used in the current analyses to measure self-reported prosocial bystander behavior at each time point.…”
Section: Someone Else Been Injured Because Of Your Drinking?)mentioning
confidence: 99%
“…An impediment to the film's ability to change men's attitudes about street harassment may be that the message is coming from a woman and is often confrontational. Not only do men appear to be more receptive to other men on topics of sexual victimization (Berkowitz, 2002), but the woman in the film can be seen as taking back power from men (or exerting power over men with her camera), which may incite a more defensive stance, particularly for those men who have more hostile attitudes toward women.…”
Section: Discussionmentioning
confidence: 99%
“…Men who participated in the perpetrator-focused program demonstrated an increase in their positive evaluation of macho behavior, rape myth acceptance and acceptance of coerced sex, whereas men who viewed the victim-focused film did not show these increases, but rather showed small decreases. Experienced prevention program developers also suggest that single-gender programs are essential since the construction and experience of masculinity increases men's appreciation for antiharassment and anti-rape messages coming from other men (Berkowitz, 2002). In fact, the Brecklin & Forde (2001) meta-analysis described above found that single-gender groups had more impact on male participants than did mixed-gender groups.…”
Section: Evaluation Of Prevention Interventionsmentioning
confidence: 99%
See 1 more Smart Citation